﻿Description of a new Promastobranchus species (Annelida, Capitellidae) from chinese coasts, with molecular evidence for intraspecific variation in the number of thoracic chaetigers - Lin, Jun Hui; García Garza, María Elena; Jian Feng, Mou; Lin, He Shan (2023)
Promastobranchus Gallardo, 1968 is a small genus in the polychaete family capitellidae, and the available records are largely reported from the Indo-West Pacific region. Although Gallardo (1968) and Green (2002) noted that Promastobranchus species had intraspecific variation in the number of thoracic chaetigers when they described the two previously known species, this variation has not been corroborated using molecular evidence. In this study, a new Promastobranchus species, Promastobranchus variabilis sp. nov., is described based on 29 specimens collected from the Beibu Gulf, South China Sea. The new species is mainly characterized by having a tessellated epithelium in the anterior thorax, nine teeth in three rows above the main fang in the abdominal hooks, four pairs of genital pores located on the intersegmental grooves between chaetigers 9 and 13, and its unique methyl green staining pattern. Comparisons of multiple gene markers (16S, 18S, 28S, and H3) revealed no genetic divergence (K2P < 0.003) among these type specimens with 9–13 thoracic chaetigers. In other words, the new species exhibited morphological variability in the number of thoracic chaetigers during ontogeny, and this character was unsuitable to differentiate Promastobranchus species as the ranges overlap among Promastobranchus species. This is the third Promastobranchus species known in the world, and it is now recorded along the Fujian coast.